Dielectric EBG Leaky-Wave Antenna: Design and Experimental Validation - Ludovica Tognolatti; Paolo Baccarelli; Cristina Ponti; Silvio Ceccuzzi; Vakhtang Jandieri; Giuseppe Schettini (IEEE Open Journal of Antennas and Propagation)
This paper proposes a novel Electromagnetic Band-Gap (EBG) leaky-wave antenna (LWA) operating in the K-band with enhanced directivity at broadside. A rigorous method that combines the analysis of the band diagrams of Bloch waves propagating within two-dimensional (2-D) EBG structures and the properties of bound and leaky modes in transversely open lattice waveguides is used to design the antenna. For the first time, a three-dimensional (3-D) realistic configuration of the EBG structure is designed, manufactured, and measured in the K-band. An effective leaky-wave approach is applied in conjunction with the use of “ad-hoc” and commercial EM full-wave software for the accurate design of the structure to be realized. The prototype consists of $7× {× }8$ alumina cylinders positioned above a ground plane and supported by two vertical metal plates. The antenna is fed by two counterphase monopoles. A rat-race hybrid junction, located just below the antenna, feeds the two monopoles. The measurements show a very good agreement with the adopted leaky-wave model. Experimental results show a broadside directivity of 12.8 dBi and a return loss of 24 dB at the frequency of $f = 24.6$ GHz. The design reported operates in the K-band in reason of its application for the project PRIN 2017 WPT4WID under grant 2017YJE9XK005.